Objektifikasi Perempuan Sebagai Elemen Persuasif dalam Iklan : Kritik Terhadap Iklan Shopee 11.11 Big Sale Versi Tukul Arwana - Prastio Ginanjar, Fahmi (CITRAWIRA : Journal of Advertising and Visual Communication, 2022)
Shopee is an e-commerce site that is engaged in buying and selling online and can be accessed easily by its consumers. Advertising is one of the most frequently used strategies in marketing. However, it often ignores ethics. The objectivity of women is one of the deviations of advertising ethics. The case study of the Shopee 11.11 Big sale advertisement, starring Tukul Arwana and background dancers wearing skimpy clothes, received a warning from KPI. Advertising is described through Swarts' holistic critique theory and then studied with the objectivity theory of Fredrickson & Roberts, then its relation to the ethical dimension by Kevin Johnston. The findings are that this advertisement contains elements of sexism and objectivity towards women and is not suitable for children